How Social Media Reviews and Perceived Value Affects the Purchase Intention of Beauty Products - Devi, Karina Vashti; Halim, Laurentia Verina (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 17 Nomor 2 Tahun 2023DO - 10.24843/MATRIK:JMBK.2023.v17.i02.p08, 2023)
This research was conducted with the aim of analyzing the green economy transition in tourism, especially tourist villages, whether it is able to provide inspiration or actually prevent an increase in people's income in conditions of the COVID-19 shock. The research was carried out in tourist villages in West Java and Lampung Provinces. This study found thatthe transition of a tourist village with the concept of green economy has a strong influence in increasing the income of rural tourism communities in conditions of the COVID-19 shock, this is due to the fact that the green economy concept encourages the utilization of natural resources and environmental preservation, this will ensure a sustainable attraction for tourists which in turn can increase revenue. Keywords: COVID-19; green economy; tourism village.